Resilience and Economic Intelligence Through Digitalization and Big Data Analytics - Dima, Alina (Proceedings of the International Conference on Economics and Social Sciences, 2021)
The International Conference on Economics and Social Sciences (ICESS)organized by Bucharest University of Economic Studies provides an opportunity for all those interested in Economics and Social Sciences to discuss and exchange research ideas. The papers presented at the Conference are available online in the Conference Proceedings series (ISSN 2704-6524). Volume 2021 Resilience and Economic Intelligence Through Digitalization and Big Data Analytics: During 2020, leaders found themselves at a historic crossroads, taking decisions under remarkable pressures and uncertainties. However, windows of opportunity are being created to shape the economic recovery, restore the health of the environment, develop sustainable business models, strengthen regional development, revitalize global cooperation, harness Industry 4.0, and redesign the social contracts, skills, and jobs.